Functions of CsGPA1 on the hypocotyl elongation and root growth of cucumbers - Yan Yan (Nature Portfolio, 2018)
Abstract G proteins regulate shoot, root, and epidermis development, as well as biotic stress tolerance in plants; however, most studies have examined model plants and less attention has been paid to the function of G proteins in horticultural plants. Here, we identified a G protein, CsGPA1, from cucumber and studied its function in seedling development of cucumbers. CsGPA1 is a peptide of 392 amino acids with a predicted molecular mass of 44.6 kDa. Spatiotemporal expression analysis found that endogenous CsGPA1 was highly expressed in roots and young leaves. Immunohistochemical assay revealed that functional CsGPA1 was present in the plasma membranes of the epidermis and cortex, and in the cytosol of the endodermis, parenchyma, and vasculature of root meristematic cells. In comparison with wild-type seedlings, CsGPA1-overexpressing transgenic lines exhibited enhanced seed germination and earlier seedling development including hypocotyl elongation and root growth. In contrast, RNAi silencing of the CsGPA1 gene inhibited seedling growth and development. Further study showed that CsGPA1 controled hypocotyl elongation and root growth via promoting cell size and the meristem of hypocotyl and root tip cells of cucumber plants. Our study expands the roles of G proteins in plants and helps to elucidate the mechanism by which cucumber regulates early seedling development.